Penetapan kadar vitamin C pada daun kelor (Moringa oleifera L.) dan bayam hijau (Amaranthus gangeticus L.) dengan metode spektrofotometri UV-Vis - Siti Maryam Indriyati; Yayuk Andayani; Anggit Listyacahyani Sunarwidhi (Universitas Mataram, 2023)
Vitamin C is a compound that cannot be formed by the body itself. Vitamin C is needed to regulate metabolic processes and normal body functions. Lack of vitamin C can cause a decrease in the immune system. During a pandemic, vitamin C is needed to improve the immune system to prevent and fight disease infections. The pandemic has caused an increase in the need and price of vitamin C supplements in the market. Fulfilling the body’s vitamin C needs can use alternatives such as Moringa leaves and green spinach. This study aims to determine the levels of vitamin C in Moringa leaves and green spinach with variations in temperature and concentration. Analysis of vitamin C was carried out using UV-Vis spectrophotometry at a wavelength of 516 nm. The results of the determination of vitamin C levels in Moringa leaves and green spinach obtained the highest levels of 24,9948% and 19,0205%, and the lowest levels of 2,2456% and 1,8710%. The results of the ANOVA test showed that there was a significant difference in the levels of vitamin C obtained at the given temperature and concentration variations.